2022
DOI: 10.21009/jtp.v24i1.23626
|View full text |Cite
|
Sign up to set email alerts
|

Developing Augmented Reality (AR) as Assisted Technology in Reading Based on Content-Language Integrated Learning

Abstract: Assisted technology has become one of the primary needs for inclusive education, especially for language learning. Language learning mediated by technology can provide affordances to EFL learners with low English language skills. Therefore, an assisted technology with content-language integrated learning was developed with the ADDIE approach to producing meaningful and motivational language learning with a dual focus, namely content and language. The materials presented in the assisted technology were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This study revealed that perceived usefulness is not a significant predicting element on the learners' attitude to use augmented reality for their English language learning. In the context of this study, the learners with low proficiency skills and homogenous abilities are prone to disregard perceived usefulness that relates to the performance improvement (Yulian et al, 2022). Another predictor namely perceived enjoyment plays influential factor how the learners accept the technology for their learning.…”
Section: Discussionmentioning
confidence: 93%
“…This study revealed that perceived usefulness is not a significant predicting element on the learners' attitude to use augmented reality for their English language learning. In the context of this study, the learners with low proficiency skills and homogenous abilities are prone to disregard perceived usefulness that relates to the performance improvement (Yulian et al, 2022). Another predictor namely perceived enjoyment plays influential factor how the learners accept the technology for their learning.…”
Section: Discussionmentioning
confidence: 93%
“…Assistive technology refers to devices or materials that can be used to help individuals with special needs and increase their functionality levels in the classroom. With the appropriate use of assistive technology, it can enhanced the effectiveness of the teaching, learning process, students' well-being, as well as creating the same opportunities and access to learning in a normal classroom (Yulian et al 2022). Therefore, in order to assist students with learning difficulties and to improve their reading skills in English subjects, teachers play an important role in determining the effective usage of technological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Students feel bored because learning is monotonous, and they only listen to the teacher explain and use existing thematic books (Fujiastuti et al, 2019;Izzaturahma et al, 2021). There is no use of technology-based learning media in schools, making teachers learn using existing books (Adnyani & Wibawa, 2021;Gultom et al, 2021;Mustaqim & Kurniawan, 2017;Yulian et al, 2022). The rest repeatedly use story books available in the school reading corner.…”
Section: Introductionmentioning
confidence: 99%